Infant with unanticipated difficult airway - Trachlight TM to the rescue - Alpna Jain; Manish Naithani (Wolters Kluwer Medknow Publications, 2012)
Lighted stylets may be used for assisting in oral intubation in both adult as well as pediatric age groups. We report the anesthetic management of an 11- month-old infant with fractured mandible where the airway was secured with tracheal lightwand-guided nasal intubation after the failure of repeated attempts of conventional laryngoscopy.